High-thermal-conductivity silica gel cap sleeve and preparation method thereof
By increasing the powder filling rate and the use of thermal conductivity of ceramic powder in the silicone cap sleeve, the problem of insufficient thermal conductivity of the existing silicone cap sleeve is solved, and a silicone cap sleeve with high thermal conductivity and high insulation strength is achieved, effectively reducing components operating temperature.
Patent Information
- Application Number
- CN202411660425.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
AI Technical Summary
The existing silicone cap covers have insufficient thermal conductivity and cannot effectively deal with high power and high heat application scenarios, resulting in excessive temperature of components and affecting service life.
By tinting and refining vinyl silicone rubber kneading glue, liquid vinyl silicone oil, dispersing agent, coupling agent, antioxidant, lubricant and thermally conductive ceramic powder, a high thermally conductive silicone cap cover is prepared and powdered The filling rate reaches 88% to 95%, and the thermal conductivity increases to 2.8~4W/m·K.
The silicone cap sleeve with high thermal conductivity, low thermal resistance and high insulation strength can effectively reduce the working temperature of components and improve service life.
Smart Images

Figure BDA0005143181680000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive interface materials, and specifically to a high thermal conductive silicone cap sleeve and a preparation method thereof. The high thermal conductive silicone cap sleeve can be used in the fields of LED, communication and new energy vehicles. The high thermal conductive silicone cap sleeve has the characteristics of high thermal conductivity, low thermal resistance and high insulation strength, and can quickly conduct heat from heat-generating components to a radiator, thereby effectively reducing the operating temperature of the components. Background Art
[0002] Thermally conductive silicone caps are widely used in heat-generating transistors, diodes, triodes, IGBTs and various columnar heat-generating interfaces due to their excellent thermal conductivity, insulation, shockproof and easy assembly properties. However, the thermal conductivity of most silicone caps currently sold on the market is only 0.3-1.2W / m·K, which is only suitable for low-power heating applications. In high-power (≥60W) and high-heat application scenarios, the temperature will be too high, seriously affecting the service life of electronic components. In severe cases, it may even directly lead to functional failure of the product. Therefore, silicone caps with higher thermal conductivity are required.
[0003] Traditional silicone caps are generally made of methyl vinyl silicone rubber raw rubber or methyl vinyl silicone rubber compound and thermal conductive powder, which are made by internal or open mixing and compression molding. The powder filling mass fraction is only 40% to 80%, and as the powder filling amount increases, the processing becomes more difficult, and the thermal conductivity of the prepared finished product is as high as 1.8W / m·K; although the powder filling mass fraction can reach 85% to 93% when prepared with liquid vinyl silicone oil, the mechanical strength of the thermal conductive silicone caps is low and the insulation strength is not high; and simply compounding methyl vinyl silicone rubber compound with liquid glue cannot well balance the relationship between thermal conductivity, insulation strength, tensile strength and elongation at break. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the object of the present invention is to provide a high thermal conductivity silicone cap and a preparation method thereof. In the present invention, vinyl silicone rubber compound, liquid vinyl silicone oil, dispersant, coupling agent, antioxidant, lubricant, thermal conductive ceramic powder are kneaded at high temperature in an internal mixer, cooled and then passed through an open mixer, a cross-linking agent and color powder are added, and then the sheet is opened and cut and molded to obtain the high thermal conductivity silicone cap.
[0005] To achieve the above objectives, the technical solutions adopted are:
[0006] One of the purposes of the present invention is to provide a high thermal conductivity silicone cap sleeve, which includes the following components, measured by weight: 15 to 40 parts of methyl vinyl silicone rubber compound, 15 to 50 parts of liquid vinyl silicone oil, 1 to 5 parts of dispersant, 1 to 5 parts of coupling agent, 0.5 to 2 parts of lubricant, 0.5 to 2 parts of antioxidant, 150 to 300 parts of 2μm spherical alumina, 300 to 600 parts of 40 micron spherical alumina, 30 to 100 parts of 0.5 micron zinc oxide, 1 to 5 parts of color powder, and 1 to 10 parts of cross-linking agent.
[0007] Furthermore, the crosslinking hardness of the methyl vinyl silicone rubber compound is SHORE A 20-40, the tensile strength is 6-8 MPa, the elongation at break is 500-800%, and the viscosity of the liquid vinyl silicone oil is 80000-300000 cp.
[0008] Furthermore, the coupling agent is at least one of vinyltrimethoxysilane, an oligomer of vinyltrimethoxysilane, vinyltriethoxysilane, an oligomer of vinyltriethoxysilane, methylvinyldimethoxysilane, an oligomer of methylvinyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, an oligomer of vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and an oligomer of vinyltriisopropoxysilane.
[0009] Furthermore, the dispersant is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and 2-methoxypolyoxyethylenepropyltrimethoxysilane.
[0010] Furthermore, the lubricant is at least one of polyethylene wax, pentaerythritol stearate, and zinc stearate.
[0011] Furthermore, the antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl]pentaerythritol ester, and dilauryl 3,3'-thiodipropionate.
[0012] Furthermore, the cross-linking agent is at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dibenzoyl peroxide, and di-tert-butylperoxide isopropylbenzene.
[0013] The second object of the present invention is to provide a method for preparing the high thermal conductivity silicone cap sleeve, comprising the following steps:
[0014] (1) 15 to 40 parts of methyl vinyl silicone rubber compound, 15 to 50 parts of liquid vinyl silicone oil, 1 to 5 parts of dispersant, 1 to 5 parts of coupling agent, 0.5 to 2 parts of lubricant, 0.5 to 2 parts of antioxidant, 150 to 300 parts of 2 μm spherical aluminum oxide, 300 to 600 parts of 40 micron spherical aluminum oxide, and 30 to 100 parts of 0.5 micron zinc oxide are mixed and stirred in an internal mixer at 40 to 100° C. at a stirring speed of 5 to 50 rpm, and vacuumed for 0.5 to 3 hours, and then taken out and cooled to obtain a mixed rubber mass;
[0015] (2) putting the mixed rubber block into an open mill, adding 1 to 5 parts of color powder and 1 to 10 parts of a cross-linking agent, and thinning the mixed rubber block on the open mill for 3 to 10 times with a gap of 0.5 to 2 mm, and then cutting the mixed rubber block into strips with a sheet size of 5 to 8 mm to obtain a rubber strip to be molded;
[0016] (3) Preheat the silicone cap mold on a molding machine at 170-220°C for 1-12 hours, then place the rubber strip to be molded on the mold and set the pressure to 30-200 kg / cm 2 , the molding time is 30 to 180 seconds to obtain a high thermal conductivity silicone cap.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The high thermal conductivity silicone cap sleeve of the present invention is prepared by selecting a methyl vinyl silicone rubber compound with suitable hardness, elongation at break and tensile strength, compounding it with a liquid vinyl silicone oil with a certain viscosity, adding a dispersant, so that the powder can be filled to a mass fraction of 88% to 95%, so that the thermal conductivity is 2.8 to 4 W / m·K, adding a coupling agent that can react with the compound, the vinyl silicone oil and the powder, and after a certain period of high-temperature treatment, the coupling agent reacts with the hydroxyl groups on the surface of the powder, and during high-temperature vulcanization, the powder can be combined with the vinyl groups on the compound and the vinyl silicone oil through covalent bonds, so that the mechanical strength of the obtained high thermal conductivity silicone cap sleeve is very high; in addition, by selecting the vinyl silicone oil with a suitable viscosity and controlling the cross-linking degree, the high thermal conductivity silicone cap sleeve can achieve a longer elongation at break and good toughness. DETAILED DESCRIPTION
[0019] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.
[0020] Example 1
[0021] 15 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 20, tensile strength 6MPa, elongation at break 500%, 15 parts of 80000cp viscosity liquid vinyl silicone oil, 1 part of dodecyl trimethoxysilane, 1 part of vinyl trimethoxysilane, 0.5 parts of polyethylene wax, 0.5 parts of tris (2,4-di-tert-butylphenyl) phosphite, 150 parts of 2μm spherical alumina, 300 parts of 40 micron spherical alumina, and 30 parts of 0.5 micron zinc oxide are mixed and stirred in a 40℃ internal mixer at a stirring speed of 5rpm, vacuumed for 0.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block is put into an open mill, 1 part of color powder and 1 part of 2,5-dimethyl-2,5-di (tert-butylperoxy) hexane are added, and the mixture is thinned 3 times on the open mill with a gap of 0.5mm, and then cut into strips with a 5mm sheet to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 170°C for 1 hour, then place the rubber strip to be molded on the mold and set the pressure to 30kg / cm 2 , molding time 30s, to obtain a high thermal conductivity silicone cap.
[0022] Example 2
[0023] 40 parts of methyl vinyl silicone rubber compound with crosslinking hardness SHORE A 40, tensile strength 8 MPa, and elongation at break 800% were mixed with 50 parts of liquid vinyl silicone oil with a viscosity of 300,000 cp, 5 parts of hexadecyl trimethoxysilane, 5 parts of vinyl trimethoxysilane oligomer, 2 parts of zinc stearate, 2 parts of tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl] pentaerythritol ester, 300 parts of 2 μm spherical alumina, 600 parts of 40 μm spherical alumina, 100 parts of 0.5 Micron zinc oxide, mixed and stirred in an internal mixer at 100℃, stirring speed 50rpm, vacuumed for 3h, taken out and cooled to obtain a mixed rubber block. Put the mixed rubber block into an open mixer, add 5 parts of color powder and 10 parts of dibenzoyl peroxide, pass it through the open mixer 10 times with a gap of 2mm, and then cut it into strips with an 8mm sheet to obtain the rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 220℃ for 12h, then place the rubber strip to be molded on the mold and set the pressure to 200kg / cm 2 , molding time 180s, to obtain a high thermal conductivity silicone cap.
[0024] Example 3
[0025] 30 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 30, tensile strength 7MPa, and elongation at break 600% were mixed with 50 parts of 160000cp viscosity liquid vinyl silicone oil, 3 parts of γ-glycidyloxypropyl trimethoxysilane, 3 parts of vinyl tri(2-methoxyethoxy)silane, 1 part of pentaerythritol stearate, 1 part of dilauryl 3,3'-thiodipropionate, 250 parts of 2μm spherical alumina, 500 parts of 40 micron spherical alumina, and 80 parts of 0.5 micron zinc oxide, mixed and stirred in an internal mixer at 70°C, stirring speed 25rpm, vacuuming for 1.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block was put into an open mill, 2 parts of color powder and 5 parts of di-tert-butyl peroxide isopropylbenzene were added, and the mixture was thinned 6 times on the open mill with a gap of 1mm, and then cut into strips with a 6mm sheet to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 180℃ for 6 hours, then place the rubber strip to be molded on the mold and set the pressure to 50kg / cm 2 , molding time 120s, to obtain a high thermal conductivity silicone cap.
[0026] Comparative Example 1
[0027] 15 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 60, tensile strength 8MPa, elongation at break 300%, 15 parts of 80000cp viscosity liquid vinyl silicone oil, 1 part of dodecyl trimethoxysilane, 1 part of vinyl trimethoxysilane, 0.5 parts of polyethylene wax, 0.5 parts of tris (2,4-di-tert-butylphenyl) phosphite, 150 parts of 2μm spherical alumina, 300 parts of 40 micron spherical alumina, and 30 parts of 0.5 micron zinc oxide are mixed and stirred in a 40°C internal mixer at a stirring speed of 5rpm, vacuumed for 0.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block is put into an open mill, 1 part of color powder and 1 part of 2,5-dimethyl-2,5-di (tert-butylperoxy) hexane are added, and the mixture is thinned 3 times on the open mill with a gap of 0.5mm, and then cut into strips with a 5mm sheet to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 170°C for 1 hour, then place the rubber strip to be molded on the mold and set the pressure to 30kg / cm 2 , molding time 30s, to obtain the silicone cap sleeve of comparative example 1.
[0028] Comparative Example 2
[0029] 15 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 15, tensile strength 4.5MPa, elongation at break 800%, 15 parts of 80000cp viscosity liquid vinyl silicone oil, 1 part of dodecyl trimethoxysilane, 1 part of vinyl trimethoxysilane, 0.5 parts of polyethylene wax, 0.5 parts of tris (2,4-di-tert-butylphenyl) phosphite, 150 parts of 2μm spherical alumina, 300 parts of 40 micron spherical alumina, and 30 parts of 0.5 micron zinc oxide are mixed and stirred in an internal mixer at 40°C, stirring speed 5rpm, vacuuming for 0.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block is put into an open mill, 1 part of color powder and 1 part of 2,5-dimethyl-2,5-di (tert-butylperoxy) hexane are added, and the mixture is thinned 3 times on the open mill with a gap of 0.5mm, and then cut into strips with a 5mm sheet to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 170°C for 1 hour, then place the rubber strip to be molded on the mold and set the pressure to 30kg / cm 2 , molding time 30s, to obtain the silicone cap sleeve of comparative example 2.
[0030] Comparative Example 3
[0031] 15 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 20, tensile strength 6MPa, elongation at break 500%, 15 parts of liquid vinyl silicone oil with viscosity of 40000cp, 1 part of dodecyl trimethoxysilane, 1 part of vinyl trimethoxysilane, 0.5 parts of polyethylene wax, 0.5 parts of tris(2,4-di-tert-butylphenyl)phosphite, 150 parts of 2μm spherical alumina, 300 parts of 40 micron spherical alumina, and 30 parts of 0.5 micron zinc oxide are mixed and stirred in a 40℃ internal mixer at a stirring speed of 5rpm, vacuumed for 0.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block is put into an open mill, 1 part of color powder and 1 part of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are added, and the mixture is thinned 3 times with a gap of 0.5mm on the open mill, and then cut into strips with a sheet of 5mm to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 170°C for 1 hour, then place the rubber strip to be molded on the mold and set the pressure to 30kg / cm 2 , molding time 30s, to obtain the silicone cap sleeve of comparative example 3.
[0032] Comparative Example 4
[0033] 15 parts of methyl vinyl silicone rubber compound with cross-linking hardness SHORE A 20, tensile strength 6MPa, and elongation at break of 500% are mixed with 15 parts of 500000cp viscosity liquid vinyl silicone oil, 1 part of dodecyl trimethoxysilane, 1 part of vinyl trimethoxysilane, 0.5 parts of polyethylene wax, 0.5 parts of tris (2,4-di-tert-butylphenyl) phosphite, 150 parts of 2μm spherical alumina, 300 parts of 40 micron spherical alumina, and 30 parts of 0.5 micron zinc oxide, and mixed and stirred in a 40℃ internal mixer at a stirring speed of 5rpm, vacuumed for 0.5h, and then taken out and cooled to obtain a mixed rubber block. The mixed rubber block is put into an open mill, 1 part of color powder and 1 part of 2,5-dimethyl-2,5-di (tert-butylperoxy) hexane are added, and the mixture is thinned 3 times with a gap of 0.5mm on the open mill, and then cut into strips with a 5mm sheet to obtain a rubber strip to be molded. Preheat the silicone cap mold on a molding machine at 170°C for 1 hour, then place the rubber strip to be molded on the mold and set the pressure to 30kg / cm 2 , molding time 30s, to obtain the silicone cap sleeve of comparative example 4.
[0034] The silicone caps obtained in various embodiments and comparative examples were tested as shown in Table 1, and the results are shown in Table 1.
[0035] Table 1. Performance results of silicone caps of examples and comparative examples
[0036]
[0037] From the above comparison data, it can be seen that the hardness of the methyl vinyl silicone rubber compound used in Comparative Example 1 is too high, the elongation at break is low, the prepared silicone cap has high hardness, low elongation, and is easy to break; the tensile strength of the methyl vinyl silicone rubber compound used in Comparative Example 2 is low, and the prepared silicone cap has low tensile strength; the viscosity of the liquid vinyl silicone oil used in Comparative Example 3 is too low, and the molecular weight is too low, resulting in reduced tensile strength; the viscosity of the liquid vinyl silicone oil in Comparative Example 4 is too high, and it is difficult to fill the thermal conductive powder, resulting in the hardness of the silicone cap rising to SHORE D level, and poor compressibility. The high thermal conductive silicone cap described in the present invention has high tensile strength and elongation, moderate hardness, good toughness, and a thermal conductivity coefficient that is much higher than that of traditional silicone cap products.
[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity silicone cap sleeve, characterized in that: The invention comprises the following components in parts by weight: 15 to 40 parts of methyl vinyl silicone rubber compound, 15 to 50 parts of liquid vinyl silicone oil, 1 to 5 parts of dispersant, 1 to 5 parts of coupling agent, 0.5 to 2 parts of lubricant, 0.5 to 2 parts of antioxidant, 150 to 300 parts of 2 μm spherical alumina, 300 to 600 parts of 40 micron spherical alumina, 30 to 100 parts of 0.5 micron zinc oxide, 1 to 5 parts of color powder and 1 to 10 parts of cross-linking agent.
2. The high thermal conductivity silicone cap sleeve according to claim 1, characterized in that: The crosslinking hardness of the methyl vinyl silicone rubber compound is SHORE A 20-40, the tensile strength is 6-8 MPa, the elongation at break is 500-800%, and the viscosity of the liquid vinyl silicone oil is 80000-300000 cp.
3. The high thermal conductivity silicone cap sleeve according to claim 1 or 2, characterized in that: The coupling agent is at least one of vinyltrimethoxysilane, an oligomer of vinyltrimethoxysilane, vinyltriethoxysilane, an oligomer of vinyltriethoxysilane, methylvinyldimethoxysilane, an oligomer of methylvinyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, an oligomer of vinyltri(2-methoxyethoxy)silane, vinyltriisopropoxysilane, and an oligomer of vinyltriisopropoxysilane.
4. The high thermal conductivity silicone cap sleeve according to claim 3, characterized in that: The dispersant is at least one of dodecyl trimethoxy silane, hexadecyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, and 2-methoxypolyoxyethylene propyl trimethoxy silane.
5. The high thermal conductivity silicone cap sleeve according to claim 1, characterized in that: The lubricant is at least one of polyethylene wax, pentaerythritol stearate and zinc stearate.
6. The high thermal conductivity silicone cap sleeve according to claim 1, characterized in that: The antioxidant is at least one of tris(2,4-di-tert-butylphenyl)phosphite, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl]pentaerythritol ester and dilauryl 3,3'-thiodipropionate.
7. The high thermal conductivity silicone cap sleeve according to claim 1, characterized in that: The cross-linking agent is at least one of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dibenzoyl peroxide, and di-tert-butyl peroxide isopropylbenzene.
8. A method for preparing the high thermal conductivity silicone cap sleeve according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) 15 to 40 parts of methyl vinyl silicone rubber compound, 15 to 50 parts of liquid vinyl silicone oil, 1 to 5 parts of dispersant, 1 to 5 parts of coupling agent, 0.5 to 2 parts of lubricant, 0.5 to 2 parts of antioxidant, 150 to 300 parts of 2 μm spherical aluminum oxide, 300 to 600 parts of 40 micron spherical aluminum oxide, and 30 to 100 parts of 0.5 micron zinc oxide are mixed and stirred in an internal mixer at 40 to 100° C. at a stirring speed of 5 to 50 rpm, and vacuumed for 0.5 to 3 hours, and then taken out and cooled to obtain a mixed rubber mass; (2) putting the mixed rubber block into an open mill, adding 1 to 5 parts of color powder and 1 to 10 parts of a cross-linking agent, and thinning the mixed rubber block on the open mill for 3 to 10 times with a gap of 0.5 to 2 mm, and then cutting the mixed rubber block into strips with a sheet size of 5 to 8 mm to obtain a rubber strip to be molded; (3) Preheat the silicone cap mold on a molding machine at 170-220°C for 1-12 hours, then place the rubber strip to be molded on the mold and set the pressure to 30-200 kg / cm 2 , the molding time is 30 to 180 seconds to obtain a high thermal conductivity silicone cap.